WI-BIO: redes de monitoramento de pacientes em ambientes de automação hospitalar utilizando o padrão IEEE 802.11 - Souza, Vinícius Samuel Valério de (2014)
The monitoring of patients performed in hospitals is usually done either in a manual or semiautomated way, where the members of the healthcare team must constantly visit the patients to ascertain the health condition in which they are. The adoption of this procedure, however, compromises the quality of the monitoring conducted since the shortage of physical and human resources in hospitals tends to overwhelm members of the healthcare team, preventing them from moving to patients with adequate frequency. Given this, many existing works in the literature specify alternatives aimed at improving this monitoring through the use of wireless networks. In these works, the network is only intended for data traffic generated by medical sensors and there is no possibility of it being allocated for the transmission of data from applications present in existing user stations in the hospital. However, in the case of hospital automation environments, this aspect is a negative point, considering that the data generated in such applications can be directly related to the patient monitoring conducted. Thus, this thesis defines Wi-Bio as a communication protocol aimed at the establishment of IEEE 802.11 networks for patient monitoring, capable of enabling the harmonious coexistence among the traffic generated by medical sensors and user stations. The formal specification and verification of Wi-Bio were made through the design and analysis of Petri net models. Its validation was performed through simulations with the Network Simulator 2 (NS2) tool. The simulations of NS2 were designed to portray a real patient monitoring environment corresponding to a floor of the nursing wards sector of the University Hospital Onofre Lopes (HUOL), located at Natal, Rio Grande do Norte. Moreover, in order to verify the feasibility of Wi-Bio in terms of wireless networks standards prevailing in the market, the testing scenario was also simulated under a perspective in which the network elements used the HCCA access mechanism described in the IEEE 802.11e amendment. The results confirmed the validity of the designed Petri nets and showed that Wi-Bio, in addition to presenting a superior performance compared to HCCA on most items analyzed, was also able to promote efficient integration between the data generated by medical sensors and user applications on the same wireless network